Plant knowledge among the remaining Pite Saami (Bidumsámegiella) speakers in Swedish Sápmi - Shelton, Deborah Aleia Aldana; Svanberg, Ingvar (Études finno-ougriennes, 2023)
This article deals with the linguistic ethnobotany among the remaining Pite Saami speakers. Only 20-40 individuals nowadays speak the language. The frequency of categories in the flora lexicon is proportional to the section of phytonyms and plant-related terms that were most available in the speakers’ vocabularies and memory. Terms surrounding trees dominate the lexicon, and they have been the easiest to remember for all speakers, as well as their uses. Flowering plants are peripheral, some plants being remembered by only one interviewed speaker. None of the interviewed speakers could remember any medical uses of flowering plants or herbs. Cet article traite d’ethnobotanique linguistique parmi les locuteurs restants du same de Pite. De nos jours, seuls 20 à 40 personnes parlent la langue. La fréquence des catégories dans le lexique de la flore est proportionnelle à la part des phytonymes et des termes en rapport avec les plantes les plus accessibles au lexique et à la mémoire des locuteurs. Le lexique est dominé par les termes relatifs aux arbres, qui ont été les plus simples à se remémorer de la part de tous les locuteurs, de même que leurs utilisations. Les plantes sont périphériques, dans certains cas seul un locuteur interviewé s’est souvenu de leurs noms. Aucun des informateurs n’a pu se rappeler de l’usage médical des plantes à fleurs ou des herbes. Denna artikel avhandlar en lexikografisk och etnobotanisk dokumentation som utfördes 2021 bland pitesamer i Sverige. Pitesamiska, som enligt UNESCO är ett akut hotat språk, talas idag av mellan 20 och 40 personer. Dokumentationen resulterade i ett floralexikon, som omfattar de växtbeteckningar och växtrelaterade termer som fanns tillgängliga i talarens ordförråd och hågkomster. Resultatet visar att termer förknippade med träd dominerade lexikonen, något som talarna uppenbarligen har haft enklast att komma ihåg. Blomväxter är däremot perifera. De intervjuade talarna kunde bara erinra sig ett fåtal sådana. Ingen av de intervjuade talarna mindes några ...